Experimental and numerical aerodynamic analysis of a low-powered car - Balbarona, Juvy A. (2011.)
Optimization of the aerodynamic performance of road vehicles has become an important subject in the automobile industry over the last century. Nearly all aerodynamic design of road vehicles relies on a combination of experimental and numerical results, and the physical understanding of flow behaviour. This study presents the experimental method and numerical approach used to determine the aerodynamic performance of a low-powered vehicle ion terms of drag force. Three dimensional CAD models of the proposed design of the car are created using PRO/Engineer Wildfire 5.0 while computational analysis and detailed flow visualizations are performed using computational fluid dynamics software. Experimental investigation by flame test on a reduced scale model of the final design is done to validate the results obtained in the numerical approach. A good agreement between measured and approximated values obtained independently using the two methods suggests the reliability of the procedures undertaken to determine the drag forces of a low-powered car over the entire range of low velocities.
Thesis (M.S. in Mechanical Engineering)--University of the Philippines, Diliman
Keywords: Automobiles -- Aerodynamics